THE ANALYSIS OF CHLORIDE IN ARGENTOMETRY ON DIG WELL WATER IN KUPANG REGENCY OF KUPANG TENGAH DISTRICT OEBELO VILLAGE IN 2014 - AGUSTINA WILHELMINA DJUMA; MARCE SELVINCE TALAEN (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2015)
The allocation of the water wich for human consumption must be of the source have clear and healthy. Limites of the source water is clear and safe it must be free from the chemistry have dangerous and poisonous is fill of minimal standard which fixes by WHO or healthy ministry of RI. Source of the water is benefited by society in the regency of Kupang four orchard village Oebelo is digging well. Beside as a tool, it is also used to be needed for salt production. This manner can be results of raising as consequence presence chloride from five results production salts which have can be blackened of dig well water by a citizen is using as source clear water to everyday needed. The aim of this research is to know a degree of chloride on dig well of water in the regency of Kupang four orchard village Oebelo. Measuring of the degree be does by Argentometry method of Mohr. According to descriptive of a result of the data analysis and appealing with Permenkes RI number 492/menkes /PER /IV /2014 about the rules of qualities water s maximum degree of chloride which is permitted in drinks water is 250 mg/L. The result of this research sample A degree of chloride 249,18 mg/L, sample B degree of chloride is 491,34 mg/L, sample C degree of chloride is 425,24 mg/L, sample D degree of chloride 173,14 mg/L and the last sample E degree of chloride is 261,46 mg/L. Three of five sample which has researched is sample B, sample C, and sample E does not fill the rules of qualities drink waters.